The Punishments for Online Gambling according to Islamic Mass Ulama - Solihah, Mar’atus; Syam, Syafruddin; Hafsah, Hafsah (Law Development Journal, 2023)
This research aims to describe punishments for online gambling according to islamic mass ulama. The type of research used in this research is a field research approach. The primary data in this research are the opinions of Ulama at the Islamic Community Organization Muhammadiyah and Nahdatul Ulama North Sumatra. And as secondary data, there is various literature in several books by several scholars Yusuf Al Qardhawi, Quraish Shihab, as well as other scientific works that support this research. The approach in this research also uses two approaches, namely the Statutory Approach and the Comparative Approach. The statutory approach (Statutory Approach) is carried out by analyzing and reviewing the legal regulations related to gambling sanctions, namely Law no. 7 of 1974 concerning Controlling Gambling, Article 303 bis Paragraph (1) of the Criminal Code, and Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions. The results of this study are the point of view of the Muhammaduyah Ulama of North Sumatra regarding punishments for online gambling perpetrators can be concluded that there are 3 punishments, namely; prison sentence, exile sentence and strict warning sentence. Meanwhile, according to the North Sumatra Nahdhatul Ulama Ulama, there are 2 punishments, namely Prison and Fine.